Alfa-Fetoprotein-Producing Female Primary Urethral Adenocarcinoma with Neuroendocrine Differentiation - Takao Natsuyama; Yozo Mitsui; Masato Uetani; Shigeyuki Ohta; Masafumi Inoue; Koichiro Akakura (Case Reports in Urology)
We report an extremely rare case of an alpha-fetoprotein- (AFP-) producing female primary urethral adenocarcinoma with neuroendocrine differentiation (NED). The patient was a 65-year-old woman with a 2-year history of urinary frequency and voiding difficulty. Enhanced computed tomography showed an approximately 3.0×5.0-cm mass around the proximal urethra and bladder neck. Of examined tumor markers, serum AFP was elevated (48.3 ng/mL), while others including carcinoembryonic antigen were within a normal range. Transurethral resection of the tumor led to a diagnosis of carcinosarcoma of the urethra, with a radical cystourethrectomy and ileal conduit formation subsequently performed. The pathological assessment was poorly differentiated adenocarcinoma in the urethra. Immunostaining showed tumor cells strongly positive for AFP. In addition, some cancer cells were positive for CD56, chromogranin A, and synaptophysin, indicating focal NED. The tumor was finally diagnosed as an AFP-producing urethral adenocarcinoma with NED. Serum AFP was immediately normalized after surgery and no sign of tumor recurrence has been noted 2 years postoperatively.